Efektivitas Penegakan Hukum Terhadap Tindak Pidana Judi Online - Rizki Nurdiansyah; Mugni Mugni; Melly Rifa’atul Lailiyah (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
The aim of this research is to find out the effectiveness of law enforcement against online gambling crimes, considering that eradicating online gambling is quite complicated because it is technology-based. Often, efforts to eradicate it have often been carried out, such as blocking online gambling sites. However, in reality this is still not optimal because until now online gambling can still be accessed. The research method used in this research is the normative juridical research method, which is a research method that focuses on the analysis of statutory regulations, legal documents and legal concepts related to a legal problem. The approach applied in this research is a conceptual approach, a type of approach that emphasizes the analytical perspective of problem solving. This approach involves understanding aspects of legal concepts that are the basis or background of the problem, and also considering the values contained in the norming of a regulation, related to the concepts used. In this research, an effort was found that can be made in terms of the effectiveness of law enforcement against criminal acts of online gambling, namely through: 1. Legal Regulation; 2. Law Enforcement; 3. International Cooperation; 4. Technology; 5. Prevention and Education; 6. Efficient Courts; and 7. Community Support. Overall, the effectiveness of law enforcement against online gambling crimes involves a series of strategies that include at least the seven points above (Legal Regulation, Law Enforcement, International Cooperation, Technology, Prevention and Education, Efficient Courts, and Community Support). Successful law enforcement efforts require a holistic approach that integrates these various elements to address the complex challenges that arise in the digital environment.